“The Sweet Sounds of the Infinite Instruments” from the Decameron - Cappuccio, Chiara (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The presence of musical lexicon, representations and images in Boccaccio›s Decameron is a well-known and recurrent element in the development of the work, despite its traditional consideration as one of the decorative elements of the plot. In this article we will try to highlight how this presence constitutes a principle of internal cohesion in the text that contributes to the maintenance of its unitary structure. With this objective, we will analyze different steps of Boccaccio›s work, related to music, highlighting the structural function they develop in the narrative. The result of these analyses confirms the centrality that music acquires in the narrative frame of the work, where Boccaccio›s literary project and the narrative purpose of the ten protagonists are expressed.  Finally, some conclusions on the Decameron musical plot will be presented, indicating its relevance for an organic reading of the literary configuration of this book.